2009
DOI: 10.1128/aac.00665-08
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Accounting for Fluoroquinolone Resistance in Escherichia coli Clinical Isolates

Abstract: Fluoroquinolone MICs are increased through the acquisition of chromosomal mutations in the genes encoding gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE), increased levels of the multidrug efflux pump AcrAB, and the plasmid-borne genes aac(6)-Ib-cr and the qnr variants in Escherichia coli. In the accompanying report, we found that ciprofloxacin, gatifloxacin, levofloxacin, and norfloxacin MICs for fluoroquinolone-resistant E. coli clinical isolates were very high and widely varied (L. Becnel Boyd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 33 publications
7
126
1
3
Order By: Relevance
“…There was a diversity of mutation patterns among the tested E. coli isolates. The S83L, D87N + S80I mutation profile has been reported to be the most prevalent in clinical settings and in the environment [13,[20][21][22][23], while the other profiles were found at low prevalence [21,23,24]; our results are in agreement with these reports. Among ParC substitutions, S80I was the most common, S80R and E84G were less frequent as previously reported [23], while L99M was described for the first time in this study.…”
Section: Discussionsupporting
confidence: 83%
“…There was a diversity of mutation patterns among the tested E. coli isolates. The S83L, D87N + S80I mutation profile has been reported to be the most prevalent in clinical settings and in the environment [13,[20][21][22][23], while the other profiles were found at low prevalence [21,23,24]; our results are in agreement with these reports. Among ParC substitutions, S80I was the most common, S80R and E84G were less frequent as previously reported [23], while L99M was described for the first time in this study.…”
Section: Discussionsupporting
confidence: 83%
“…The results of previous studies indicated that the rate of resistance to ciprofloxacin is higher than levofloxacin among Enterobacteriaceae (21,22). However, in our study, all isolates resistant to ciprofloxacin were also resistant to levofloxacin but the average MIC for ciprofloxacin was higher than levofloxacin that indicate levofloxacin is slightly more effective against K. pneumoniae isolates.…”
Section: Discussioncontrasting
confidence: 54%
“…Two of these water molecules are coordinated by a conserved serine and acidic residue (located four positions downstream) in the A subunit of the enzyme. Substitutions in the residues that anchor the bridge are the most prevalent cause of quinolone resistance (10)(11)(12)(13)(22)(23)(24)(25)(26)(27). In most species, the serine is mutated far more often than the acidic residue.…”
Section: D94gmentioning
confidence: 99%